Le identità nazionali nell'Unione Europea - Amato, Giuliano (Lectio Magistralis, 2018)
This Reading aims at recreating the evolution of the seventy-year-long history of integration, of the complex and changing balance between the reasons behind the safeguarding of national identities and interests and those behind the "research" and "creation of common interests".